Blunt trauma: An uncommon cause of common bile duct injury. Issue 5 (October 2015) - Sanford, Zachary; Abdolmaali, Kamran; Robinson, Dustin; Denning, David
Abstract: Blunt force trauma to the extrahepatic biliary ductal system as a cause of avulsion is an uncommon injury associated with wide variability in prognosis. These cases are often difficult to identify, primarily as they are complicated by trauma patients exhibiting more immediate and obviously life-threatening injuries. This case demonstrates a 46 year-old-male involved in a head on motor vehicle collision, sustaining blunt force abdominal trauma resulting in partial transection of the common bile duct. Injury was discovered incidentally on exploratory laparotomy post endovascular repair of abdominal thoracic aortic rupture. Open cholescystectomy with intraoperative cholangiogram was performed, isolating extravasation from the common bile duct. A 16-French T-tube was placed in the common bile duct and two large #24 Jackson-Pratt tubes were placed in the vicinity. The procedure was well-tolerated and the patient was discharged with T-tube in place. Discharge was on postoperative day 28 with removal of tubes on postoperative day 54 and the patient was able to make a full recovery.